Recent advances in zinc-based chalcogenides for potassium ion batteries - Xijun Xu; Tao Yang; Fangkun Li; Shaomin Ji; Jingwei Zhao; Yanping Huo; Jun Liu (Resources Chemicals and Materials)
Lithium-ion batteries (LIBs) gradually occupied the energy storage market due to their long cycling life, high working voltage, as well as energy density. However, LIBs have high costs due to the limited lithium resource and difficulty to exploit. Potassium ion batteries (PIBs) have aroused extensive attention over the past few years since they possess considerable potassium salt resources while exhibiting similar electrochemical properties to LIBs. The electrode material takes on great significance in determining the properties exhibited by the batteries. Zinc-based chalcogenides have served as the most suitable anode materials for their numerous raw material resources, low prices, and environmental friendliness. Nevertheless, the application of Zinc-based chalcogenides has been continuously hindered by sluggish diffusion kinetics, low electrical conductivity, as well as huge volume variation. Several effective strategies have been explored to settle the above matters (e.g., designing nanostructures, constructing carbon composite structures, as well as doping anions or cations to construct heterojunction). In this review, the recent advance of zinc-based chalcogenides (e.g., electrochemical mechanisms, challenges, and perspectives) are summarized. This review can provide novel insights into the development of transition metal chalcogenides for PIBs.